2021
DOI: 10.1021/acs.chemmater.1c02234
|View full text |Cite
|
Sign up to set email alerts
|

Unusually High Electron Affinity Enables the High Oxidizing Power of Layered Birnessite

Abstract: Two-dimensional layered birnessite is a powerful natural oxidant for many species such as water, metal cations, and organic contaminants and plays an important role in many biogeochemical cycles. Herein, the factors responsible for its high oxidative activity were evaluated through a series of seven birnessites with interlayer cations of H, Li, Na, K, Cs, Ca, and Mg along with other MnO x polymorphs. Results show that the oxidative activity of birnessite, which decreases in the order Mg > Cs = K > Na > Ca > L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 86 publications
1
18
0
Order By: Relevance
“…Cs‐bir showed Cs peaks without the presence of K. Li‐bir showed a small weak peak indicating that some K may be left behind even after 48 h exchange, which is consistent with prior observations [22] . The XRD patterns of these powders were reported in our previous study, [3] and show that they conform to the standard pattern of a birnessite‐type lattice without the presence of secondary phases. Using the peak at the 2 θ value of approximately 12°, the interlayer d‐spacing of Li‐bir, K‐bir, and Cs‐bir was determined to be 7.17 Å, 7.27 Å, and 7.57 Å, respectively.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Cs‐bir showed Cs peaks without the presence of K. Li‐bir showed a small weak peak indicating that some K may be left behind even after 48 h exchange, which is consistent with prior observations [22] . The XRD patterns of these powders were reported in our previous study, [3] and show that they conform to the standard pattern of a birnessite‐type lattice without the presence of secondary phases. Using the peak at the 2 θ value of approximately 12°, the interlayer d‐spacing of Li‐bir, K‐bir, and Cs‐bir was determined to be 7.17 Å, 7.27 Å, and 7.57 Å, respectively.…”
Section: Resultssupporting
confidence: 74%
“…The reason for the spontaneous dissolution of birnessite is likely related to its unusual band structure. Results of our recent study [3] show that many cation‐exchanged birnessites possess unusually large electron affinities of around 6.0 eV in aqueous solution, which puts their CB well below the redox potential of the O 2 /H 2 O reaction. The band structure (Figure 6) was determined by using previously measured values of the work function (flat band potential) and band gap ( E g ) through electrochemical Mott‐Schottky and absorption spectroscopy measurements, respectively, and accounting for the differences in the electrolyte pH by assuming Nernstian behavior for the band edges.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…), [82][83][84][125][126][127][128][129][130][131] our results are at odds with that interpretation for the oxidation of Co(II) to Co(III). We found that Co(II) sorbed on a vacancy site (…”
Section: Mnmentioning
confidence: 57%
“…According to the predictive thermodynamic models explored in this study, Co­(II) is not oxidized on MnO 2 layer edges but on vacancy sites on basal planes. Vacancy sites are known to form strong TCS complexes with divalent metals and to be involved in electron exchange reaction with Mn­(III) and Mn­(IV). ,,,,, ,,,, They facilitate photoconductivity and photoreductive dissolution of the MnO 2 layer. ,, Although Mn­(III) has a strong electron affinity and is usually regarded to mediate the oxidative activity of birnessite, whether it is bonded over a vacancy (Mn TCS 3+ ) or is incorporated in the lattice (Mn Layer 3+ ), , our results are at odds with that interpretation for the oxidation of Co­(II) to Co­(III). We found that Co­(II) sorbed on a vacancy site (Co TCS 2+ ) is oxidized to Co INC 3+ by a layer Mn­(IV) in the vacancy.…”
Section: Discussionmentioning
confidence: 99%